2012
DOI: 10.1530/eje-11-1119
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of acromegalic patients with hyperprolactinemia and the differences in patients with merely GH-secreting adenomas: clinical analysis of 279 cases

Abstract: Objective: The aim of this study is to evaluate clinical data from a large cohort of acromegalic patients with and without hyperprolactinemia. Design and methods: Between January 2002 and June 2010, a set of data on 279 acromegalic patients undergoing transsphenoidal surgery was available. Based on preoperative GH and prolactin (PRL) levels, patients were divided into GH and GHCPRL groups. A stabilization or a further improvement of postoperative changes in clinical, hormonal, immunohistochemical, and magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 38 publications
1
35
2
5
Order By: Relevance
“…[11,12] The second case displays the idea of GH control in a newly diagnosed case of macroprolactinoma. [13,14,15] The IGF1 (Insulin Growth Hormone 1) is a screening test in every new case of pituitary adenoma (with reference levels adjusted based on patient' s age and sex). [13,14,15] Since the levels of IGF1 may vary an oral glucose tolerance test is useful especially in tumours larger than 1 cm diameter since acromegaly displays in 80-90 % of cases a macroadenoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[11,12] The second case displays the idea of GH control in a newly diagnosed case of macroprolactinoma. [13,14,15] The IGF1 (Insulin Growth Hormone 1) is a screening test in every new case of pituitary adenoma (with reference levels adjusted based on patient' s age and sex). [13,14,15] Since the levels of IGF1 may vary an oral glucose tolerance test is useful especially in tumours larger than 1 cm diameter since acromegaly displays in 80-90 % of cases a macroadenoma.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14,15] The IGF1 (Insulin Growth Hormone 1) is a screening test in every new case of pituitary adenoma (with reference levels adjusted based on patient' s age and sex). [13,14,15] Since the levels of IGF1 may vary an oral glucose tolerance test is useful especially in tumours larger than 1 cm diameter since acromegaly displays in 80-90 % of cases a macroadenoma. [13,14,15] Prolactin-GH cosecretion is found in one tenth of acromegaly cases with a phenotype suggesting either prolactinoma or acromegaly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent paper by Wang et al (61) has reported that women with GH-PRL-secreting adenomas often have relatively low serum GH levels and that these adenomas are associated with higher incidences of menstrual disorders and galactorrhoea compared with GH-secreting adenomas. In patients with hyperprolactinaemia, we found that three of 78 patients developed acromegaly (58).…”
Section: Gh Excess and Hyperprolactinaemiamentioning
confidence: 99%